Sex for Grades: Untold Stories of Sexual Harassment in Institutions of Higher Learning in Nigeria - Adesoji, Joseph Oluyemi; Adijat, Joseph Adejoke; Patrick, Osho Olanrewaju; Aliu, Bello Ayodeji; David, Fagbamila Olumide; Emmanuel, Atolagbe; Olawande, Fagbamila (Papers in Education and Development, 2024)
This study examined sexual harassment in higher learning institutions in Nigeria. Diverse forms of sexual harassment experienced by respondents in higher institutions, the perceived causes, incidence, prevalence, and consequences on respondents were examined. Three hundred respondents recruited through the multistage sampling method participated in the study, while the data was retrieved through questionnaires. Almost half (49.7%) of the respondents in the study were sexually harassed in school, out of which, (48.3%) were sexually harassed more than once. Verbal sexual harassment topped the list of forms of sexual harassment (25.5%), while wearing seductive dresses ranked as the highest perceived cause of sexual harassment with (81.2%). Sexual harassment was most prevalent in public universities, while respondents were mostly angered when they were sexually harassed with (27.5%) even though (18.1%) were terrified while (16.8%) felt violated. Keywords: Sexual harassment, universities, fear, violated, Nigeria.